Irradiation of VFAT3: a 128-channel charge-sensitive front-end device for the CMS GEM phase-2 upgrade. (1st April 2022) - Irshad, A.; Aspell, P.; De Lentdecker, G.; Licciulli, F.; Robert, F.; De Robertis, G.; ,
Abstract: VFAT3 is a 128-channel charge-sensitive front-end ASIC explicitly designed for the CMS GEM phase-2 upgrades. LHC is undergoing major upgrades for HL-LHC, where the particle rate is expected to increase up to 5 times with respect to the nominal LHC luminosity of 10 34 cm −2 s −1 . It is, therefore, necessary to monitor the evolution of the VFAT3 response due to aging in the radiation environment by total ionizing dose (TID) test. The device operation could also be interrupted by a single high-energy particle. Thus, the estimation of the single event upset (SEU) cross-section is essential as well. We summarize irradiation test results that validate the suitability of VFAT3 for CMS GEM upgrade.